Growth Inhibition Effect of Syzygium aromaticum Ethanol Extract on Methicillin-Resistant Staphylococcus aureus - Tsabita Rana Kamila; Rike Syahniar; Indriyani Indriyani; Shinta Dewi Permata Sari (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2025)
Background: MRSA is the leading cause of death caused by antimicrobial resistance. The distribution of MRSA occurs globally, and the incidence rate is around 30 per 100,000 people per year. Cloves had antimicrobial properties that were tested in both resistant and susceptible clones. Purpose: To determine the growth inhibition effect of clove flower ethanol extract on the growth of Methicillin-Susceptible Staphylococcus aureus (MSSA) and Methicillin-Resistant Staphylococcus aureus (MRSA). Methods: This research uses an experimental design. Clove extract will be analyzed using gas mass chromatography-spectrometry (GC-MS). MSSA isolate was taken from S.aureus ATCC 25913, and MRSA was taken from nasal swabs. The concentrations of the ethanol extract of cloves used are 20%, 40%, 60%, 80%, and 100%. All ethanol extract concentrations from cloves will be tested using the Kirby-Bauer disc diffusion technique. The magnitude of the barrier zone determines the antibacterial properties. Results: The results of the GC-MS analysis showed three main antibacterial compounds, including eugenol, phenol, and caryophyllene. The average inhibitory zones of the antibacterial test at concentrations of 20%, 40%, 60%, 80%, and 100% clove flower ethanol extract against MSSA were 16 mm, 16.33 mm, 17.67 mm, 18.33 mm, and 18.33 mm, respectively. The results of the average calculation of the inhibition zone in MRSA according to each concentration of clove flower ethanol extract were 11 mm, 12 mm, 13 mm, 14.33 mm, and 15.67 mm. Conclusion: Cloves have antibacterial properties, as confirmed by studies showing a zero zone in the MSSA and MRSA antibacterial sensitivity test, with the best concentration being 100% ethanol extract. The study's results show that the antibacterial effect of cloves affects MSSA more than MRSA.